SINERGI PROMOSI VISUAL DAN DIGITAL: BANNER, STIKER KEMASAN, DAN GOOGLE MAPS BAGI UMKM KERIPIK SINGKONG - Anisa Aprilia Dewi; Ratu Sukma Rupawan; Dita Eka Setiani; Rakha Agust Pratama Subiantono (CV. Kalimasada Group, 2025)
The Community Service Program (PKM) through the Student Community Service (KKN) of Universitas Muhammadiyah Lampung (UML) was carried out to strengthen the promotion and branding capacity of the cassava chips micro-enterprise “Manggleng Bu RT” in Wates Village, Pringsewu, Lampung. The activities were designed using a Participatory Action Research (PAR) approach, which emphasizes the direct involvement of business actors in each stage. The intervention focused on three simple yet effective strategies: (1) creating a banner as a visual promotional medium in the surrounding environment, (2) optimizing packaging with branded stickers to strengthen product identity, and (3) registering the business location on Google Maps to expand consumer reach and enhance digital visibility. The activities were implemented in five stages: initial coordination, needs assessment, design co-creation, production and procurement, as well as handover and training on managing the digital profile. The results demonstrated an improvement in the promotional readiness of the MSME through the availability of banners and stickers, along with the establishment of a digital identity that makes it easier for consumers to find the business location. Conceptually, this synergy of visual and digital promotion is relevant to recent literature emphasizing the importance of simple branding, minimum digital presence, and local promotion strategies for the sustainability of MSMEs. This program recommends replicating the minimum promotion for other food-based MSMEs in rural–urban areas as an initial step towards sustainable digital transformation.